Darurat Literasi di Era Kurikulum Merdeka melalui Transformasi Pembelajaran Bahasa Indonesia untuk Meningkatkan Efektivitas Belajar Siswa SMP - Akmalia Putri; Sahrul Muzekki; Tatik Maryana (Jurnal Cendekia Pendidikan, 2026)
This study aims to describe the implementation of the *Merdeka Belajar* (Freedom to Learn) Curriculum in Indonesian language classes, analyze student learning effectiveness following its implementation, and identify the factors supporting and hindering its execution in class VIII-F at SMP Negeri 3 Sampang. The study employs a descriptive qualitative approach using a case study design. Data were collected through interviews, observations, and documentation, while data analysis followed the Miles, Huberman, and Saldana (2019) model, comprising data reduction, data display, and conclusion drawing. The results indicate that the implementation of the *Merdeka* Curriculum at the school has been quite effective. The Indonesian language teacher employs differentiated and project-based learning, supported by the principal through policies regarding teacher training and the development of teaching modules. Student learning effectiveness improved in terms of engagement, motivation, and comprehension of the material, although participation was not yet uniform. Supporting factors for implementation include school policy support, teacher collaboration, and student enthusiasm, whereas inhibiting factors include limited facilities, disparities in student abilities, and the administrative workload placed on teachers.